2012
DOI: 10.1182/blood-2011-10-388736
|View full text |Cite
|
Sign up to set email alerts
|

CD86 is expressed on murine hematopoietic stem cells and denotes lymphopoietic potential

Abstract: IntroductionA large body of information exists about molecular mechanisms involved in maintaining HSC integrity, and many studies have identified unique markers associated with differentiation. 1 However, several of these parameters differ between strains of mice or change dramatically according to developmental age, activation status, or inflammation. [2][3][4] This issue gained importance with the realization that HSCs are normally heterogeneous and that functionally distinct subsets can be resolved accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 50 publications
1
36
1
Order By: Relevance
“…4 In contrast, CD412 HSCs were found to be enriched for lymphoid-associated factors such as ikzf1, ikzf2, notch1, notch2, flt3, and il7ra, as well as CD86, which has been recently found to denote lymphopoietic potential of HSCs. 41 Analysis of HSC lineage bias in vivo confirmed the observations that CD41 marks myeloid-biased HSCs. The fact that the lineage distribution differences between CD41:YFP1 and CD41:YFP2 fractions were less evident in secondary recipients could have several interpretations.…”
Section: Discussionmentioning
confidence: 61%
“…4 In contrast, CD412 HSCs were found to be enriched for lymphoid-associated factors such as ikzf1, ikzf2, notch1, notch2, flt3, and il7ra, as well as CD86, which has been recently found to denote lymphopoietic potential of HSCs. 41 Analysis of HSC lineage bias in vivo confirmed the observations that CD41 marks myeloid-biased HSCs. The fact that the lineage distribution differences between CD41:YFP1 and CD41:YFP2 fractions were less evident in secondary recipients could have several interpretations.…”
Section: Discussionmentioning
confidence: 61%
“…Interestingly, among lymphoid-related genes, Rag1 , which is indispensable for both T and B cell differentiation, was strongly induced by Satb1 (Figure 5C). Expression of the CD86 gene that correlates with lymphoid competency (Shimazu et al, 2012) was also significantly elevated.…”
Section: Resultsmentioning
confidence: 99%
“…Our prior studies indicated that loss of CD86 and CD18 together with increases in CD41 and CD150 defines HSC that accumulate in aged or chronically LPS treated animals [15], [16]. Even in untreated adult mice, such HSC are poor with respect to lymphocyte formation and probably overlap with myeloid-skewed HSC identified in single cell transplantation experiments [5]–[7].…”
Section: Discussionmentioning
confidence: 99%